2021
DOI: 10.1088/1361-6595/abe91c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of non-thermal dielectric barrier discharges at atmospheric pressure in presence of microfibrillated cellulosic foams

Abstract: Plasma processing of sustainable polymers from renewable resources has recently gained significant interest. This work reports the ignition of plane-to-plane dielectric barrier discharges at atmospheric pressure operated in nominally high-purity helium with microfibrillated cellulose (MFC) foams derived from woody biomass taking up the entirety of the gas gap. Over the whole range of experimental conditions examined, discharge ignition and propagation mostly occurs through the foam from one electrode to the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Over the last two decades, low-temperature atmospheric pressure (AP) plasmas have gained increasing interest as versatile tools for the surface engineering of many different materials [33][34][35]. Interestingly, recent studies have shown the remarkable potential of AP plasma processes for the effective surface modification of 3D porous materials [25,[36][37][38][39][40][41][42][43] Up until now, few works have been dedicated to the use of AP plasmas for the preparation of functional materials to be used in oil/water separation [41,[44][45][46][47]. Examples in the literature mainly focus on the surface processing of filtration materials, such as polymer or metal meshes, polymer membranes and cotton fabrics [45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, low-temperature atmospheric pressure (AP) plasmas have gained increasing interest as versatile tools for the surface engineering of many different materials [33][34][35]. Interestingly, recent studies have shown the remarkable potential of AP plasma processes for the effective surface modification of 3D porous materials [25,[36][37][38][39][40][41][42][43] Up until now, few works have been dedicated to the use of AP plasmas for the preparation of functional materials to be used in oil/water separation [41,[44][45][46][47]. Examples in the literature mainly focus on the surface processing of filtration materials, such as polymer or metal meshes, polymer membranes and cotton fabrics [45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%